Work and breast milk feeding: a qualitative exploration of the experience of lactating mothers working in ready made garments factories in urban Bangladesh - A M Rumayan Hasan; George Smith; Mohammad Abdus Selim; Shahinoor Akter; Nazib Uz Zaman Khan; Tamanna Sharmin; Sabrina Rasheed (International Breastfeeding Journal, 2020)
Abstract Background In Bangladesh 65% of children under 6 months of age were exclusively breastfed with maternal employment being a risk factor that has jeopardized exclusive breastfeeding. As Ready Made Garment (RMG) factories have been the largest employer of low income women in Bangladesh, the objective of our study was to explore the barriers and facilitators of breastfeeding and perceptions about use of expressed breast milk among mothers who worked in the RMG sector. Methods This formative research was conducted during July–September 2015 in two slums of Dhaka among RMG workers who were mothers and the caregivers of 0–12 month old infants. Qualitative data was obtained from purposively selected participants of 8 in-depth interviews and 4 focus group discussions (mothers and caregivers), and 2 key informant (RMG factory official) interviews. Mothers were from multiple RMG factories while factory officials were from a single factory. Thematic analysis was conducted. Results The main themes of qualitative exploration were knowledge and experience of breastfeeding; structural barriers (home and workplace); consequences of inadequate breastfeeding; and perception and experience of using expressed breast milk. Despite knowledge both of the benefits of breast milk and of the importance of breastfeeding for 6 months, most mothers introduced formula as early as 2 months to prepare for their return to work. Barriers such as excessive workload, inadequate crèche facilities at work, and lack of adequate caregivers at home impeded exclusive breastfeeding. Mothers and caregivers had very little knowledge about the use of expressed breast milk and were concerned about contamination. Conclusion As RMG factories are the largest employer of low-income women in Bangladesh, facilitating RMG factory working mothers’ ability to use breast milk could help to promote infant health and help women remain in the workforce.